2014
DOI: 10.1021/es5044547
|View full text |Cite
|
Sign up to set email alerts
|

Particle Size Distribution of Halogenated Flame Retardants and Implications for Atmospheric Deposition and Transport

Abstract: This study investigates the distribution of polybrominated diphenyl ethers (PBDEs), hexabromocyclododecane (HBCD) and a group of novel flame retardants (NFRs) on atmospheric aerosols. Two high volume cascade impactors were used to collect particulate fractions of ambient air over a one year period at urban and rural sites. The majority of FRs were found on the finest aerosols (<0.95 μm). Concentrations of HBCD were higher than those of ΣPBDEs. Moreover, we noted seasonality and spatial differences in particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
41
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 81 publications
12
41
1
Order By: Relevance
“…The mass concentrations of PM determined in this study were almost at the same level as those measured in earlier studies in Beijing, China (Zhao et al, 2005), Guangzhou, China (Duan et al, 2007), and some Indian cities (Sharma and Maloo, 2005). However, the PM mass concentrations in this study were much higher than those reported in Shanghai, China , the Czech Republic (Okonski et al, 2014), Nagoya, Japan (Kadowaki and Naitoh, 2005), Western Europe and North America (Sharma and Maloo, 2005) and Illmitz, Austria (Barmpadimos et al, 2012).…”
Section: Quality Assurance/quality Controlsupporting
confidence: 79%
See 2 more Smart Citations
“…The mass concentrations of PM determined in this study were almost at the same level as those measured in earlier studies in Beijing, China (Zhao et al, 2005), Guangzhou, China (Duan et al, 2007), and some Indian cities (Sharma and Maloo, 2005). However, the PM mass concentrations in this study were much higher than those reported in Shanghai, China , the Czech Republic (Okonski et al, 2014), Nagoya, Japan (Kadowaki and Naitoh, 2005), Western Europe and North America (Sharma and Maloo, 2005) and Illmitz, Austria (Barmpadimos et al, 2012).…”
Section: Quality Assurance/quality Controlsupporting
confidence: 79%
“…The distribution patterns of organic pollutants in airborne particles (Ni and Zeng, 2013;Okonski et al, 2014) or dust (Cao et al, 2014;Wang et al, 2013a,b) have raised concern recently. However, to date, there has been no research on the size-specific distributions of PCNs in PM fractions in the atmosphere.…”
Section: Size-specific Distributions Of Pcns In Pm Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another crucial factor affecting particle-bound concentrations of NPOCs is their aerodynamic diameter ). The size-specific distributions of compounds are dependent on their physical-chemical properties, gasparticle partitioning and photodegradation (Okonski et al, 2014;X. Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Because their semi-volatile nature is considered to be a good repository of their explicit large surface area (Cao et al, 2014). These semi-volatile FRs have the potential to be partitioned between gas and particulate phases in the air being important for their environmental fate (Okonski et al, 2014). Moreover, the coarse and fine particles are the main contributor to the deposition (wet and dry) processes of the particle-bounds FRs.…”
Section: Introductionmentioning
confidence: 99%